The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ol.2017.6707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate biomarkers for epithelial ovarian cancer metastasis using microarray data

Abstract: Abstract. Epithelial ovarian cancer (EOC) is a common cancer in women worldwide. The present study assessed effective biomarkers for the prognosis of EOC metastasis. The GSE30587 dataset, containing 9 EOC primary tumor samples and 9 matched omental metastasis samples, was analyzed. Following normalization, the differentially expressed genes (DEGs) between these samples were identified using the limma package for R. Subsequently, pathway enrichment analysis was performed using ClueGO, and a protein-protein inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…A similar tendency, as seen in the current study, with COL3A1 protein was seen in a previous study in that expression was higher in a highly proliferative ovarian carcinoma cell line than in a low malignant potential one (Gagné et al 2007 ). COL3A1 gene has also been found differentially expressed between primary ovarian carcinomas and metastases (Li et al 2017 ). Le Page and colleagues showed that BMP2 was differentially transcribed between cells derived from ascites and solid tumours (Le Page et al 2006 ) whilst Hibbs and colleagues suggested BMP7 was more highly expressed in ovarian carcinomas than normal ovaries, but was unable to distinguish between ovarian tumour tissues and metastasis (Hibbs et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar tendency, as seen in the current study, with COL3A1 protein was seen in a previous study in that expression was higher in a highly proliferative ovarian carcinoma cell line than in a low malignant potential one (Gagné et al 2007 ). COL3A1 gene has also been found differentially expressed between primary ovarian carcinomas and metastases (Li et al 2017 ). Le Page and colleagues showed that BMP2 was differentially transcribed between cells derived from ascites and solid tumours (Le Page et al 2006 ) whilst Hibbs and colleagues suggested BMP7 was more highly expressed in ovarian carcinomas than normal ovaries, but was unable to distinguish between ovarian tumour tissues and metastasis (Hibbs et al 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kim SH et al demonstrated that ECM-receptor interaction led to direct or indirect control of cell adhesion, migration, differentiation, proliferation and apoptosis [43]. ECM-receptor interaction was reported to be related to esophageal squamous cell carcinoma [44] and epithelial ovarian cancer [45]. In addition, focal adhesion signaling hubs critically regulated cell behavior, impacted on tumor cell survival and served as potential cancer targets [46].…”
Section: Discussionmentioning
confidence: 99%
“…ECM-receptor interaction pathway enrichment was reported in esophageal squamous cell carcinoma [23]. Li et al found multiple DEGs and miRNAs were potential biomarkers for the prognosis of epithelial ovarian cancer (EOC) metastasis through the ECM-receptor interaction pathway [24] and affected tumor prognosis [25]. XuS et al found that prostaglandin E2 (PGE2) receptor EP4 signaling activates the cyclic (c)-AMP signaling pathway, which may be closely related to the occurrence of prostate cancer [26].…”
Section: Discussionmentioning
confidence: 99%